A fatal cobra-bite in a snake expert - Hossain, MZ; Atiqullah, S; Saha, AC; Chowdhury, AJ; Jahangir, KM; Faiz, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):303-7. The abstract of this article is available on the PubMed website